Management Strategies for the Improvement of Management and Teaching Leadership in the Cajamarca Region, 2023. - Mendoza Sánchez, J.R. (2025)
The management and leadership of an educational institution must respond to a planned idea guided by the mission and vision of the organization, which is why the formulation of plans and strategies locate the actions of managers in Cajamarca. This formulation helps to achieve institutional objectives and fulfill its social mission. The proposal of this work is made up of four strategies to improve the management culture of the leadership of directors and teachers in the institution. In this sense, the problem is described based on the existence of managers lacking the capacity to prioritize adequate pedagogical and institutional management.